2019
DOI: 10.3390/molecules24142644
|View full text |Cite
|
Sign up to set email alerts
|

Novel Derivatives of Deoxycholic Acid Bearing Linear Aliphatic Diamine and Aminoalcohol Moieties and their Cyclic Analogs at the C3 Position: Synthesis and Evaluation of Their In Vitro Antitumor Potential

Abstract: A series of novel deoxycholic acid (DCA) derivatives containing aliphatic diamine and aminoalcohol or morpholine moieties at the C3 position were synthesized by 3,26-epoxide ring-opening reactions. These compounds were investigated for their cytotoxicity in four human tumor cell lines and murine macrophages and for inhibitory activity against macrophage-mediated NO synthesis in vitro. Obtained data revealed that: (i) all amine-containing substituents significantly increased the cytotoxicity of the novel compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…37 NO is an important intracellular and intercellular signaling molecule that is involved in regulating a variety of physiological and pathophysiological processes. 38 Under normal conditions, NO can regulate physiological functions such as neurotransmission, vasodilation and immune response. However, excessive intracellular NO is not conducive to alleviating the inflammatory response and can damage cells and lead to apoptosis.…”
Section: Papermentioning
confidence: 99%
“…37 NO is an important intracellular and intercellular signaling molecule that is involved in regulating a variety of physiological and pathophysiological processes. 38 Under normal conditions, NO can regulate physiological functions such as neurotransmission, vasodilation and immune response. However, excessive intracellular NO is not conducive to alleviating the inflammatory response and can damage cells and lead to apoptosis.…”
Section: Papermentioning
confidence: 99%
“…Eleventhly Markov et al [24], illustrated that compound 9 in a series of innovative DCA obtained substances possessing an aliphatic diamine andaminoalcohol/ morpholine moiety present at the C3 region, led to apoptosis along with autophagy in HuTu80 duodenal carcinoma cells (Figure 3L). They illustrated that compound 9 results in ROS based cell demise by activation of intrinsic caspase based pathway of apoptosis along with cell destroyer autophagy in HuTu80 duodenal carcinoma cells.…”
Section: Cell Death Modes Of Synthetic Bile Acids Prototypical Agents...mentioning
confidence: 99%
“…Additionally, various laboratories have generated innovative Bile Acid obtained substance for evaluation of the tumor suppressive actions of bile acids. These substances were illustrated to result in induction of programmed cell death (PCD) in different cancer cells besides possess tumor repressive action [14][15][16][17][18][19][20][21][22][23][24]. Cell death possesses a key part in embryonic formation, sustenance of homeostasis, as well as elimination of injured cells.…”
Section: Introductionmentioning
confidence: 99%
“…Eleventh, Markov et al [32] showed that compound 9, among a series of novel DCA derivatives containing an aliphatic diamine and aminoalcohol or morpholine moiety at the C3 position, induces apoptosis and autophagy in HuTu-80 duodenal carcinoma cells (Figure 3L). They showed that compound 9 causes ROS-dependent cell death by activating the intrinsic caspase-dependent pathway of apoptosis and cell-destructive autophagy in HuTu-80 duodenal carcinoma cells.…”
Section: Cell Death Mechanism Of Synthetic Bile Acid Derivatives In C...mentioning
confidence: 99%
“…In addition, several laboratories have synthesized novel bile acid derivatives to explore the tumor-suppressive function of bile acids. These derivatives were shown to induce programmed cell death in several cancer cells, and have tumor-suppressive effects [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%